Identification of Land Adequacy for Green Open Space Development area of Tanjung Barangan on the condition of land properties in Palembang - Linda Utami; Satria Jaya Priatna; Dadang Hikmah Purnama (Research Centre of Inorganic Materials and Complexs, 2018)
The city of Palembang is one of the cities that experienced rapid development and became the center of human activity. So that the expansion of the city to the periphery causes green open space reduction. The reduction of green open space inflicted the disruption of the balance between nature and human systems. Retention ponds include reduction of green open space border that serves as a drainage system so as to prevent flooding during the rainy season and maintain groundwater reserves during the dry season. This study aims to: 1) identify and evaluate the existing condition of soil properties (physical and chemical) in the green open space development area of Tanjung Barangan retention pond in plan area that will be functioned as a retention pond of Palembang City; 2) to see the relation between the physical and chemical of soil condition with the type of vegetation that will be developed in the area of green open space development plan; 3) recommend the appropriate vegetation types to be developed in the green open space development plan, retention pond area in Palembang City. This research used descriptive normative method and sampling was done by sample purposive sampling. The research was conducted in the administrative area of Palembang City, the sampling point was in the green open space development area of Tanjung Barangan retention pond in Bukit Baru Village, Ilir Barat 1 Subdistrict of Palembang City, there were 4 (four) research sample points. It can be concluded that based on the results of laboratory analysis and direct observation in the field, the condition of soil properties of green open space development plan area of Tanjung Barangan retention pond physically and chemically that was: average effective depth value belong to deep (> 100 cm); soil texture of clay loam, clay and loam; platy and granular soil structures; soil color gray, yellowish brown to black; moderate to moderately rapid soil permeability; soil pH strongly acidic N-total low to moderate; Soil P2O5 is very low; K2O is very high; and C-organic is low to very high. Based on the results of the analysis, the recommendation of vegetation type from the Minister of Public Works Regulation No. 5 of 2008 showed that The Tanjung Barangan retention ponds contain 3 (three) types of vegetation recommended namely casuarina (Casuarina equisetifolia), coconut (Cocos nucifera) and fern tree (Filicium decipiens). While there were 4 (four) types of vegetation can be recommended with the condition of the soil management by calcification using agricultural lime, such as lime tohor (CaO), calcite (CaCO3) or dolomite (CaMg (CO3)2) which is munding rubber vegetation (Ficus elastica), mangosteen (Garcinia mangostana), bungur (Lagerstroemia speciosa) and resin (Agathis loranthifolia).